Estimation of vibration and force stimulus thresholds for haptic guidance in MIS Training (2011)
This manuscript investigates the minimum perception thresholds for force and vibration stimuli in a simple movement pattern and using the same haptic device. The model was model derived from the well-known Up-Down Transformed Response Rule varying the force magnitude and the amplitude of vibration feedback. It was demonstrated that the vibration sensitivity was around ﬁ fteen times smaller than the force threshold. The results were compared with previous published studies for different tasks, experimental conﬁ gurations and devices. We concluded that the type of task signiﬁ cantly affects human detection threshold for force and vibration feedback, and should be adapted for the design of a new haptic-based skill transfer system for minimally invasive surgery (MIS) using haptic guidance.